Clinicopathological study of gall bladder cancer and its relationship with gall stones - R Poudel (Society of Surgeons of Nepal, 2016)
Introduction: Gall bladder cancer is the most common cancer of the biliary tree and one of the highly malignant tumors with poor prognosis. Although its incidence is low in west, it is common in our part of the world. There are very few studies regarding gall bladder cancer in Nepal. The incidence of gallstones in patients with gall bladder cancer is high. The aim of the study was to evaluate the clinicopathological aspect of the disease in patients with gallbladder cancer and to Asses the incidence of gallstones in patients with gall bladder cancer.